Norma internacional contable NIC 38 y los activos intangibles en Colombia (2015)
The implementation of international accounting standard IAS 38 Intangible Assets, brings several criteria for defining identifiers that assets of this nature are part of the company through their recognition and measurement. Establishes standards for the valuation of intangible assets,its economic assessment and representative within the company or entity. Its application in Colombia against Decree 2649 of 1993 developed and supplemented accounting policy, but in comparison between the two standards is emphasized marked the exclusion of Good Will as an intangible asset difference. The accounting treatment of intangible assets framing principles in order to achieve a goal directly linked in decision -making in corporate executives, financial information that reveals its measurement, establishes requirements to consider and possible effects cause by new revelations.